Geographic variations in a model of physician treatment choice with social interactions - Mary A. Burke; Gary M. Fournier; Kislaya Prasad (Federal Reserve Bank of Boston, 2009)
Location-specific norms of behavior are a widespread phenomenon. In the case of medical practice, numerous studies have found that geographic location exerts a strong influence on the choice of treatments and procedures. This paper shows how the presence of social influence on treatment decisions can help to explain this phenomenon. We construct a theoretical model in which physicians' treatment choices depend on atients' characteristics and on the recent choices of nearby peerseither because there are local knowledge spillovers or because physicians want to conform to local practice patterns. In our model, regional differences in the patient mix give rise to geographically divergent treatment patternsthe treatment a patient receives depends on where she lives. Investigation of Florida data reveals significant geographic variation in treatment rates consistent with the predictions of our model. Implications for patient welfare are explored.
Keywords: C73; Z13; I10; I11; 330; geographic variations in medicine; evolutionary game theory; interacting particle systems; social influence; local interactions; medical practice guidelines; Evolutionäre Spieltheorie; Soziale Beziehungen; Gesundheitsversorgung; Räumliche Verteilung; Theorie